Does double trigger (GnRH-agonist + hCG) improve outcome in poor responders undergoing IVF-ET cycle? A pilot study. (3rd July 2019) - Haas, Jigal; Zilberberg, Eran; Nahum, Ravit; Mor Sason, Aya; Hourvitz, Ariel; Gat, Itai; Orvieto, Raoul
Abstract: Many strategies are offered for the treatment of poor responders. However, no compelling advantage for one stimulation protocol over another has been hitherto established. In this study, we aimed to evaluate the role of different modes and timings of final follicular maturation trigger, on in vitro fertilization (IVF) cycle outcome of poor responder patients. In the present randomized controlled study, poor responder patients, according to the Bologna criteria, undergoing controlled ovarian hyperstimulation (COH) using the gonadotropin-releasing hormone (GnRH) antagonist protocol were randomly assigned to three different final follicular maturation trigger modes and timings: hCG 36 h before oocyte pick-up (OPU) (hCG trigger); GnRH agonist (GnRHag) 36 h before (OPU) and hCG on day of OPU (GnRHag trigger); and GnRHag and hCG, 40 and 34 h prior to OPU, respectively (double trigger). Pregnancy rate, number of oocytes, and top quality embryos (TQEs). Thirty-three poor responder patients were recruited and randomized to the different study groups. While there were no in-between groups' differences in patients' demographics and stimulation variables, patients in the double trigger group had a significantly higher number of TQE (1.1 ± 0.9 vs . 0.3 ± 0.8 and 0.5 + 0.7; p <.02) as compared to the hCG trigger and the GnRH-ag trigger groups, respectively, with an acceptable pregnancy rate. Double trigger offers an additional benefit to poor responder patients. Larger studies are required to support this new concept prior to its implementation to IVF practice. Trial registration: ClinicalTrials.gov identifier: NCT02144818.